Platelet hyaluronidase 2 enrichment in acute coronary syndromes: a conceivable role in monocyte-platelet aggregate formation - Vinci, Ramona; Pedicino, Daniela; D'Aiello, Alessia; Ciampi, Pellegrino; Ponzo, Myriana; Bonanni, Alice; Russo, Giulio; Montone, Rocco Antonio; Massetti, Massimo; Crea, Filippo; Liuzzo, Giovanna (Journal of enzyme inhibition and medicinal chemistry, 2021)
Acute Coronary Syndromes (ACS) with plaque erosion display dysregulated hyaluronan metabolism, with increased hyaluronidase-2 (HYAL2) expression. However, the expression and the role of this enzyme on platelets has never been explored. We evaluated the platelet's HYAL2 ( plt HYAL2) levels on I) stable angina (SA) and II) ACS patients, furtherly sub-grouped in Intact-Fibrous-Cap (IFC) and Ruptured-Fibrous-Cap (RFC), according to Optical Coherence Tomography. We assessed the HYAL2 role through an in vitro model setting of co-cultured monocytes and platelets, before and after treatment with low-molecular-weight hyaluronic acid (HA) as pro-inflammatory stimulus and with or without HYAL2-antibody to inhibit HYAL2 activity. ACS patients exhibit higher plt HYAL2 levels comparing to SA, with the higher expression for IFC group. The addition of HYAL2-antibody significantly reduced the percentage of monocyte-platelet binding, suggesting that plt HYAL2 enrichment at the site of the culprit lesion is a key mediator in the systemic thrombo-inflammatory status of ACS presenting with plaque erosion. Representation of platelet Hyaluronidase 2 involvement in monocyte-platelet aggregates and pathogenesis of plaque erosion. (Ab, antibody; ECM, extracellular matrix; EC, endothelial cells, HYAL2, hyaluronidase 2; LMW-HA, low molecular weight-hyaluronan)